The formation of the treaty law of non-international armed conflicts - Perna, Laura (International humanitarian law series, 2006)
Aims to trace the processes that led to the formation of the treaty norms applicable in non-international armed conflicts. This study analyses questions such as: where does the international law of internal armed conflicts come from? Why did it evolve differently from the law regulating international armed conflicts?